An overview of floral and vegetative evolution in the Asian clade of Bulbophyllum (Orchidaceae) - Thawara, Nicha; Kongsawadworakul, Panida; Suksathan, Piyakaset; Watthana, Santi; Pingyot, Thitiporn; Merckx, Vincent S.F.T.; Ruchisansakun, Saroj (Plant ecology and evolution, 2024)
Background and aims – Bulbophyllum , the largest genus in Orchidaceae, exhibits a diverse morphology in both reproductive and vegetative characters. While trait diversity and evolution has been extensively studied in Malagasy species and within the Cirrhopetalum alliance clade, the evolution of reproductive and vegetative characters at the whole level of the Asian clade remains largely unexplored. Material and methods – We reconstructed the phylogeny of approximately 11% of all Asian Bulbophyllum species using Bayesian inference and maximum likelihood estimation based on nuclear (ITS) and chloroplast ( mat K, psb A- trn H) DNA sequence data. This phylogenetic framework allowed us to examine the evolution of two vegetative and four floral characters through ancestral state reconstruction. Key results and conclusion – The ancestral character states of the Asian clade of Bulbophyllum include a single leaf, distinct pseudobulbs, multiple-flowered inflorescences, and lateral and dorsal sepals similar in length. One-leaved pseudobulbs evolved into two-leaved pseudobulbs multiple times. Distinct pseudobulbs gave rise to indistinct pseudobulbs twice. Multiple-flowered inflorescences shifted to solitary flowers and 2–3-flowered inflorescences multiple times, with some instances of evolutionary reversal. Lateral sepal elongation also presents a convergent evolutionary scenario.